INCIDENCE AND MORTALITY OF CERVICAL CANCER IN THE OMSK REGION - O. P. Goleva; Z. B. Tasova; O. P. Prudnikova (Сибирский онкологический журнал)
The purpose of the study was a comparative assessment of the cervical cancer incidence and mortality among females in urban and rural populations of the Omsk region.Material and Methods. The study included females aged over 18 years from urban and rural areas of the Omsk region. According to population-based cancer registry data for the period 2004–16, the crude cancer incidence and mortality rates in urban and rural populations were calculated. The variational and correlation analyzes were used, the differences were assessed using Student t-test.Results. During 2004–16, the cervical cancer incidence among females of the Omsk region showed an increasing tendency, reaching a peak incidence in women aged 35–54. Concerning the cervical cancer mortality rate, it tended to decrease. For rural females, the cervical cancer mortality rate decreased from 10.8 to 9.7 per 100,000 females (p>0.05). For urban females, the mortality rate decreased from 9.2 to 7.5 per 100,000 females (p>0.05). No significant differences in the mortality rates between urban and rural females were found (p>0.05). The tendency towards decreased incidence of advanced cervical cancer (the average decrease being 3.3 % for rural females and 2.8 % for urban females, p>0.05) and increased incidence of early stage cervical cancer (the average rise being 1.8 % and 1.9 %, respectively) was observed.Conclusion. In the Omsk region, the cervical cancer mortality rate for both rural and urban females showed a tendency to decrease. During the study period, the incidence of cervical cancer had increased; however the incidence of advanced cervical cancer had decreased.